The impact of fascist thought on the Egyptian political movements 1930-1939 (The Muslim Brotherhood and maser al Fataat ) as a model - Hussein, Zainab Khaled (Journal of Tikrit University for Humanities, 2023)
The importance of the research entitled (The Impact of Fascist Thought on Egyptian Political Movements 1930-1939) (Frères Musulmans and Egypt Girl) as a model, is that it sheds light on an important time period in which intellectual trends were active that came from political parties in Egypt influenced by what was proposed by the fascist movement in Italy, which It included nationalist ideas represented in restoring the glories of the Roman Empire, and the Egyptian parties quoted (Frères Musulmans) and Egypt Girl) those ideas and made them part of its partisan creed and tried to apply them to restore the glories of the Egyptian Empire, which consisted of Egypt and Sudan at the time, but the repercussions of the Second World War that occurred later have aborted these ideas after the end of the fascist era in Italy.